Post a New Question

Algebra

posted by on .

Use the quadratic formula to find the real solutions:

2x/x-3 + 2/x = 3
I know I multiply both sides by x(x-3), but I don't know how to do that.

  • Algebra - ,

    rewrite the equation as ...
    [2x/(x-3)](x(x-3)) + [2/x](x(x-3)) = 3(x(x-3))

    notice in the first term, x-3 on top cancels x-3 at the bottom, in the second term x on top cancels x at the bottom , to get ...
    2x(x) + 2(x-3) = 3x^2 - 9x
    2x^2 + 2x - 6 = 3x^2 - 9x
    x^2 - 11x + 6 = 0

    x = (11 ± √97)/2

  • Algebra - ,

    thank you!

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question